Examining the Predictive Role of School Climate on Mathematical Efficacy: Insights from Indonesian PISA 2022 Data - Tarmidi Tarmidi; Maria Theresa Hutapea; Muhammad Rozan Alfarisi (Didaktik Matematika, 2025)
Mathematics is a key discipline across many fields; however, data indicate that students' mathematical competence in Indonesia remains below optimal levels. One potential factor influencing this competence is students' self-efficacy in mathematics. Schools play a critical role in fostering a positive climate that enhances students' mathematics self-efficacy. This study examines the influence of school climate on students' mathematics self-efficacy in Indonesia, utilizing secondary data from the PISA 2022 dataset. The sample includes 13,439 Indonesian students, selected through a stratified proportional random sampling method. Data collection was conducted using a PISA-developed scale, tested for validity and reliability. Multiple linear regression analysis was employed, producing a significant model, F(4, 12,253) = 77.594, p < .00, R = .025. These results indicate that school climate has a substantial predictive role on variations in students' mathematics self-efficacy. Specifically, factors such as school belongingness, perceived safety, and evaluation of safety risks partially influence mathematics self-efficacy. However, experiences of bullying showed no significant effect. The findings highlight the critical role of students' psychological perceptions of their school environment in shaping their self-efficacy in mathematics, emphasizing the importance of fostering positive school climates to support students' academic success.